Protective activity of Basella alba l. Leaf extract on cardiac injury markers following intestinal ischemia-reperfusion: potential for cardiovascular therapy - Olubayode Bamidele; Oyinkansola Fasipebi; Eniola E. Tomoloju; Lawrence D. Adedayo; Ayodeji F. Ajayi; Ayobami O. Afolabi (Pharmaceutical Science Advances)
Intestinal ischemia-reperfusion injury (IIRI) is a serious pathological condition that not only causes local damage to the intestine but also contributes to injury in distant organs such as the heart. Basella alba, a commonly consumed leafy vegetable with known antimicrobial, anti-inflammatory, and antioxidant properties in traditional medicine, is believed to have protective effects against such injuries. This study aimed to investigate the cardioprotective potential of methanol extract of Basella alba leaves in male Wistar rats subjected to IIRI. Thirty male Wistar rats (200–250g) were divided into five groups. Group A (sham operated) received normal saline (10 ​mg/kg) for two weeks. Group B was subjected to IIRI and also received normal saline. Groups C and D were pretreated with Basella alba extract at 100 ​mg/kg and 200 ​mg/kg, respectively, before IIRI. Group E received vitamin C (200 ​mg/kg) prior to IIRI induction as a standard control. The study assessed cardiac oxidative stress parameters, inflammatory and cardiac injury markers, alongside histological evaluation. Results revealed that Basella alba-pretreated groups and the vitamin C group had increased levels of antioxidant enzymes—superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)—and reduced malondialdehyde (MDA), a lipid peroxidation marker. Inflammatory markers including myeloperoxidase (MPO), interleukin-1β, interleukin-6, and tumor necrosis factor-α were significantly reduced, while interleukin-4 levels were elevated. Cardiac injury markers such as troponin C and creatine kinase-MB were also significantly decreased. Histological assessment confirmed the biochemical findings, showing improved heart tissue architecture in treated groups. In conclusion, methanol extract of Basella alba demonstrated significant cardioprotective effects against IIRI, comparable to vitamin C at high dose. These findings support its traditional use and suggest its dietary inclusion could benefit individuals at risk of heart injury due to IIRI.